Empirical model of textile water retention in professional washing machines. Issue 10 (26th September 2022) - Battistella, Nicola; Furlan, Federico; Gardonio, Paolo; Gallina, Paolo; Simonato, Michele
Abstract: This paper presents an experimental study and proposes an empirical model on the residual water content of a cotton load during the extraction phase of professional washing machines. Literature lacks data about spinning dewatering performances and thus a method is proposed to measure and predict water retention with respect to the main parameters that affect the washing process. The paper first provides a survey about retention models developed for different applications. It then introduces a new methodology to estimate residual moisture content as a function of time and centrifugal parameters, which avoids time consuming measurements. The methodology is proposed with respect to a customised washing cycle, which enables experimental validation with commercial washing machines. A scaling analysis is finally performed to verify the influence of the drum shape on retention performances. Results confirm the validity and versatility of the proposed model on a wide range of professional washing machines.